THE SPIRITUAL LEVEL OF THE COMMUNITY OF EAST KALIMANTAN, INDONESIA, DURING THE COVID-19 PANDEMIC - Yusuf, Muhammad; Hamka, Hamka (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
In several countries, including Indonesia, and East Kalimantan, people are not prepared to deal with Covid-19, so they are afraid of getting infected with Covid-19. East Kalimantan ranks 7th in Indonesia and has the highest Covid-19 infection rate outside of the island of Java. The high number of Covid-19 infections naturally affects the psyche of people in East Kalimantan. Hence, people in East Kalimantan need to improve their spirituality, so they do not have to worry. This study aimed to assess the level of community spirituality during the Covid-19 infection. The method used in this study is quantitative analysis with description using SPSS 25.0 software (n = 538, age = 18-60 years) by online questionnaire. The results of the study showed that the level of spirituality of people in East Kalimantan was low for both men and women. This caused disruption to social interaction, anxiety, and stress. However, the people of East Kalimantan have embraced and accepted the situation and hope that the government can defeat the Covid-19 pandemic.